INTEGRASI KURIKULUM MERDEKA TERHADAP KARAKTER MANUSIA DALAM KONSEP AL-QUR’AN - Mutiara, Elvian; Betty Mauli Rosa Bustam (CV. ADIBA AISHA AMIRA, 2024)
The existence of curriculum changes seeks to continue to advance education in Indonesia in terms of intellectual and character. But the fact that Indonesian education still prioritizes intellectual rather than character, this can be seen from the lack of application in character education itself. Therefore, this study aims to examine more deeply the integration of the independent curriculum currently applied in the world of education with the concept of the Qur'an in shaping human character. The method used in this research is a library research with data sources obtained through various references in the form of journals, books, proceedings, and relevant articles. The results of this study explain that the formation of human character in the world of education is limited to the curriculum system, but the curriculum used must also be in accordance with the concept of the Qur'an in shaping human character.